A Case Study of Children Language Acquisition: The Form of Questions-Making Processes Employed by Preschoolers: - - Hakim, Furqanul; Artha, Berli; Chiani, Saraswati Haylian (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study shows the forms of questions making by 3 and 5 years old children. Purposive sampling was used to determine the objects of the study.. The forms were found through descriptive qualitative approach by implementing three methods, observation, interview, and note taking techniques to collect the data. To analyze the data, the researchers used data reduction, categorization, and conclusion. The researchers confirmed that there were four kinds of questions-making processes employed by Preschoolers. They were sign form, single word form, double word form or phrase, and clause or sentence.  It can be concluded that the differences between those two ages were in term of the frequency of using the forms. The 3 years old child used single and double word forms frequently, while the 5 years old child used double word form or phrase and clause frequently.